BASIC CONCEPTS OF ORGANIZATIONAL STRUCTURE - Nurul Hidayati Murtafiah; Putri Intan Yulianti; Imam Nurjaman; Ridwan (CV Naskah Aceh, 2024)
Organizing is a process of classifying and dividing activities/work according to the expected goals of an organization, so that by organizing tasks and responsibilities can be divided among the administrators so that everything can run effectively. In organizing this article, we review the factors that influence it, namely: Human Resources, Goals and Organizational Structure. a study of Human Resource Management literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: (1) Human or human resource management in an organization influences the organizing process related to the implementation of the organization itself. (2) Organizational goals influence organizing, where in its activities the organization must be oriented towards organizational goals. (3) The organizational structure influences organizing because the organizational structure regulates, including the division of tasks and authority, in a simple organizational concept map.